2014
DOI: 10.1111/jfb.12378
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of Lampanyctus crocodilus on north‐west Mediterranean Sea slopes in relation to reproductive cycle and environmental variables

Abstract: This study examined the population structure, reproductive cycle and feeding pattern of the lanternfish Lampanyctus crocodilus in the Balearic Basin (north-west Mediterranean Sea) from a depth of 450 to 1800 m and at a seasonal scale. Juveniles were mainly located at shallower depths, but also at deepest stations in autumn, while adults mostly inhabited intermediate depths with their centre of population density (CPD) located at 800-1000 m of depth. The migration of adults to deeper depths was detected in late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 90 publications
(154 reference statements)
1
10
0
Order By: Relevance
“…In any case, the distribution of trophic positions among myctophid species in this and other studies reflects their opportunism in consuming different prey. For example, investigations on B. glaciale of similar sizes to those studied here (30-42 mm) and from different regions showed similar TPA, 3.3 in the subpolar North Atlantic (Petursdottir et al, 2008), between 3.5 and 3.8 in the western Mediterranean (Fanelli et al, 2014;Valls et al, 2014), and 3.3 in our study (Table 2,TPA). Mean values of TPA reported for other species in the western Mediterranean, such as M. punctatum, L. dofleini, D. holti, and L. pusillus (Fanelli et al, 2011(Fanelli et al, , 2014Valls et al, 2014), also differed by less than 0.3 trophic positions of the equivalent estimates of the same species in our study.…”
Section: Trophic Positionsupporting
confidence: 83%
See 1 more Smart Citation
“…In any case, the distribution of trophic positions among myctophid species in this and other studies reflects their opportunism in consuming different prey. For example, investigations on B. glaciale of similar sizes to those studied here (30-42 mm) and from different regions showed similar TPA, 3.3 in the subpolar North Atlantic (Petursdottir et al, 2008), between 3.5 and 3.8 in the western Mediterranean (Fanelli et al, 2014;Valls et al, 2014), and 3.3 in our study (Table 2,TPA). Mean values of TPA reported for other species in the western Mediterranean, such as M. punctatum, L. dofleini, D. holti, and L. pusillus (Fanelli et al, 2011(Fanelli et al, , 2014Valls et al, 2014), also differed by less than 0.3 trophic positions of the equivalent estimates of the same species in our study.…”
Section: Trophic Positionsupporting
confidence: 83%
“…More recent studies based on bulk stable carbon (δ 13 C) and nitrogen (δ 15 N) signatures have determined the trophic levels of several species in the Tasman Sea (Flynn and Kloser, 2012), Mediterranean Sea (Fanelli et al, 2011;Valls et al, 2014), and Gulf of Mexico (McClain-Counts et al, 2017). Scattered information on isotopic values of myctophids collected in general foodweb structure studies or in diet analysis of top predators are also frequently reported (Nilsen et al, 2008;Cherel et al, 2010;Fanelli et al, 2011Fanelli et al, , 2014Colaço et al, 2013;Quintana-Rizzo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is an important prey of several bony and cartilaginous fishes, birds, and marine mammals (see Balart and Castro-Aguirre, 1995 and references cited therein), and constitutes an important vector in the energy transfer in the marine environment, not only in shallow water but also in the bathyal system. The direct relationship observed between prey abundance and food consumption in bathyal predators Fanelli and Cartes, 2008;Papiol et al, 2014) suggests that B. tanneri and P. planipes coexist at some depth stratum where P. planipes is considerably abundant. Although it is commonly accepted that the distribution of P. planipes is mainly limited to the upper 500 m, at least 250 m shallower than B. tanneri, it is likely that P. planipes is widely distributed at depths below 700 m because: 1) it was found during this investigation in 60% of the hauls made below 700 m, 2) B. tanneri has never been collected shallower than ca.…”
Section: Feeding Habitsmentioning
confidence: 99%
“…It is likely that males are capable of fertilizing more than one female thanks to their faster spermatophore production when compared to eggs production (Mauchline, 1972) and to the ability of females to store spermatophores (Nagaraju, 2011). Bathymetric changes in the sex ratio are also common among deepsea decapod crustaceans (e.g., Chilari et al, 2005;Follesa et al, 2007) and likely result of a combination of feeding and reproductive processes (Puig et al, 2001;Cartes et al, 2008;Fanelli and Cartes, 2008). The bathymetric patterns of sex distribution nevertheless seem a species-dependent adaptive strategy linked to location.…”
Section: Population Structurementioning
confidence: 99%
“…Studies of teleost reproduction are needed for fisheries management of endemic species (Abedi, Shiva, Mohammadi, & Malekpour, ; Fanelli, Papiol, Cartes, & Rodriguez‐Romeu, ; Giulianini, Luca, Valli, & Pizzul, ). The growth characteristics and feeding habits of T. stenura were investigated in the Nujiang River, China (Deng, Yue, Chen, Tian, & Liu, ) and there are a few papers concerning the biology of the Triplophysa species from the Tibetan Plateau, China (Liu, Xie, Zheng, & Ji, ; Qi et al., ; Xie, ).…”
Section: Introductionmentioning
confidence: 99%